Drug delivery : fundamentals & applications - Hillery, Anya M, Ed. Park, Kinam, Ed (CRC Press, 2017)
This book provides a comprehensive introduction to advanced drug delivery and targeting, covering their principles, current applications, and potential future developments. This edition has been updated to reflect significant trends and cutting-edge advances that have occurred since the first edition was published. All the original chapters have been retained, but the material therein has been updated. Eight new chapters have been added that deal with entirely new technologies and approaches.